IbM Pengolahan Sampah Plastik Dalam Rangka Pemberdayaan Masyarakat Kelurahan Muktiharjo Kidul Semarang - Wahyuhastuti, Novika; Indiworo, Rr. Hawik Ervina; Burhanudin, Aan (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2017)
Community service activities of science and technology program for Plastic Waste Processing Society isimplemented as a form of concern for environmental sustainability. Given the plastic waste is waste that takes time todecompose 50-100 years. On the other hand the potential of plastic waste in Pedurungan Sub-district of Semarang is verylarge. If plastic waste can be processed and managed optimally it will greatly reduce the amount of plastic waste in thearea, besides also can increase people's income. This activity was held in Muktiharjo Kidul Village, PedurunganSubdistrict, Semarang. Participants of 30 people who are members of KSM Mandiri Santoso Jaya and KSM Tri AsihJaya. Implementation in the form of (1) Socialization of Ibm's program of activity; (2) Manufacture of plastic garbagedisposal machines; (3) Training of the use of plastic counter machine; and (4) Assistance for consultation. The methodsused from socialization to mentoring are lectures, frequently asked questions, and practices. IbM activities are getting agood response marked by the antuasiasme of the participants in following every stage of the activity. The result of thisdedication activity is the reduction of plastic waste amount by recycle effort, increasing the family income throughincreasing the economic value of plastic waste, increasing the quality of activity in the garbage bank